2020
DOI: 10.3390/ani10040548
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of Lactobacillus plantarum or Macleaya cordata Extract Alleviates Oxidative Damage Induced by Weaning in the Lower Gut of Young Goats

Abstract: Weaning usually leads to stress in livestock, which has a negative impact on their growth and development. Research on oxidative stress and inflammation induced by weaning has not been reported in goats. Here, we focused on oxidative stress profile and inflammation status of the lower gut (jejunum, ileum, and colon) of goats. First, we illustrated the status of antioxidant activity and inflammation in the intestine of young goats on pre-(2 weeks postnatal, 2 wkpn) or post-(11 wkpn, weaning at day 45 postnatal)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 36 publications
0
19
0
3
Order By: Relevance
“…The supplementation of Akkermansia muciniphila can be a helpful strategy to reduce the production of oxidative stress along with the modulation of gut microbiota in streptozotocin-induced diabetic experimental rats' model [67]. Furthermore, the consumption of Lactobacillus plantarum together with Macleaya cordata extract reduced the production of intestinal oxidative stress and protect the intestinal mucosal barrier in goat [68]. Hence, it is concluded that the consumption of probiotic bacteria might act as biological barrier to produce ROS, inhibiting the ROS producing enzymes, stimulating the antioxidant enzymes, enhancing the production of antioxidant metabolites and regulating antioxidant signaling pathways and gut microbiota [69,70].…”
Section: Oxidative Stress Modification Through Nutrients and Microbiotamentioning
confidence: 99%
“…The supplementation of Akkermansia muciniphila can be a helpful strategy to reduce the production of oxidative stress along with the modulation of gut microbiota in streptozotocin-induced diabetic experimental rats' model [67]. Furthermore, the consumption of Lactobacillus plantarum together with Macleaya cordata extract reduced the production of intestinal oxidative stress and protect the intestinal mucosal barrier in goat [68]. Hence, it is concluded that the consumption of probiotic bacteria might act as biological barrier to produce ROS, inhibiting the ROS producing enzymes, stimulating the antioxidant enzymes, enhancing the production of antioxidant metabolites and regulating antioxidant signaling pathways and gut microbiota [69,70].…”
Section: Oxidative Stress Modification Through Nutrients and Microbiotamentioning
confidence: 99%
“…Malondialdehyde (MDA) is a marker of oxidative stress, reflecting the degree of lipid peroxidation. Chen et al observed that Lactobacillus plantarum additive reduced MDA in jejunum and ileum of young goats ( p < 0.01), increased SOD activity in ileum ( p < 0.01) and increased GSH‐PX activity in jejunum ( p < 0.05) (Chen et al, 2020). Liao et al showed that feeding basal diet supplemented with Clostridium butyricum can increase GSH concentration in duodenal and ileal mucosa, decrease MDA concentration in duodenal mucosa and improve SOD activity in the ileal mucosa of broilers ( p < 0.05) (Liao et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Como já observado em outras espécies (VRUBLOVA et al, 2010;SOLER et al, 2016;CHEN et al, 2020), o fitoterápico à base de Macleaya cordata teve efeito anti-inflamatório local, sendo que todos os grupos tratados mantiveram a espessura de parede intestinal dentro da normalidade para pôneis (SIWINSKA et al, 2017).…”
Section: Discussionunclassified
“…Um de seus principais ingredientes ativos é a Sanguinarina (SG), um alcalóide de benzofenantridina que possui efeitos biológicos múltiplos, sendo os principais antibiótico e anti-inflamatório (DVORAK et al, 2006;DVORÁK E SIMÁNEK, 2007). O efeito anti-inflamatório mostrou-se útil em quadros de colite induzida (VRUBLOVA et al, 2010), apresenta efeito protetivo contra processos de isquemia (WANG et al, 2017) e diminui os efeitos do estresse do desmame (CHEN et al, 2020).…”
Section: Introductionunclassified
See 1 more Smart Citation